2021
DOI: 10.1212/cpj.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Teleneurology Expansion in Response to the COVID-19 Outbreak at a Tertiary Health System in New York City

Abstract: ObjectiveTo assess the implementation of teleneurology (TN), including patient and clinician experiences, during the coronavirus respiratory disease 2019 (COVID19) pandemic.MethodsWe studied synchronous (video visit) and asynchronous (store-and-forward, patient-portal evaluation, remote monitoring) TN utilization in the Mount Sinai Health System Neurology Department in New York, 2 months before and after the start of our department's response to the pandemic in mid-March 2020. Weekly division meetings enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…However, the digital divide may not be the sole explanation for our results, particularly among Medicaid beneficiaries. At our institution, a diverse population of Medicaid-insured patients are treated in hospital-administered clinics by resident and fellow trainees under the supervision of attending neurologists (2). Because many trainees were deployed to inpatient services for COVID-related care during the first several months of the COVID surge (2) and only returned to in-person office visits in June 2020, Medicaid-insured patients were likely unable to find available providers during the initial 3 months of the COVID pandemic between March and May 2020.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the digital divide may not be the sole explanation for our results, particularly among Medicaid beneficiaries. At our institution, a diverse population of Medicaid-insured patients are treated in hospital-administered clinics by resident and fellow trainees under the supervision of attending neurologists (2). Because many trainees were deployed to inpatient services for COVID-related care during the first several months of the COVID surge (2) and only returned to in-person office visits in June 2020, Medicaid-insured patients were likely unable to find available providers during the initial 3 months of the COVID pandemic between March and May 2020.…”
Section: Discussionmentioning
confidence: 99%
“…This time interval was defined as the "pre-COVID period, " with March 16 th , 2020 marking the beginning of our Department's administrative procedures to mitigate virus transmission risk in the setting of the emerging public health threat related to the pandemic and the issued shelter-in-place order in New York State. These procedures consisted of converting scheduled in-person visits to video TN visits or deferral of care and have been described elsewhere (2).…”
Section: Data Source and Cohort Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there has been growing need for efforts to improve remote evaluation and management of patients with neurologic complaints. The use and acceptance of teleneurological consultations have been increasing (125,126), and it is encouraging that observable neurological signs, which are feasible for remote assessment, appear to have better inter-rater reliability than elicitable signs, which often require direct contact with the patient (127). Since virtual HINTS and the Dix-Hallpike maneuver have been demonstrated to be applicable via telemedicine (110), solutions for additional components of the oculomotor exam may be developed and implemented.…”
Section: Challenges and Opportunities For Pcs Diagnostic Accuracy In The Context Of The Coronavirus Disease 2019 (Covid-19) Pandemicmentioning
confidence: 99%
“…The six identified key service process factors and themes among clinicians and patientsThe rst key service process factor, technical issues, was raised mainly by clinicians who reported signi cant gaps in this area, especially regarding functionality, reliability, availability, accessibility, system exibility, technical support, and training [26,47,47,49,[53][54][55]. For instance, clinicians indicated that patients' technological capacity was a barrier to successful teleconsultation[26,55].…”
mentioning
confidence: 99%